Theology and society in context: a theologist's reflections on selected topics - Asante, Emmanuel (SonLife Press, 2014)
"A compilation of professor Asante's articles, sermons and reflections on some of the many issues related to the interconnections between theology and national life ... He brings one to the hard conclusion that, the Christian's life and his theology cannot be separate from his life as an individual at the workplace, in church, ministry and even in politics."–Back cover
Keywords: Christianity and culture; Christianity and politics; Church and state; Ghana